Factors Associated with Independence for Elderly People in Their Activities of Daily Living - Sri Wahyuni; Christantie Effendy; Fitrina Mahardani Kusumaningrum; Fatwa Sari Tetra Dewi (Universitas Airlangga, 2021)
Background: Health in the elderly does not merely refer to a condition free from disease but should also have elements regarding functionality and independence. Purpose: This study aimed to measure Activities of Daily Living (ADLs) and to identify the factors affecting ADLs among the elderly population in Sleman District. Methods: A cross-sectional study was carried out using secondary data from the Multidimensional Elderly Care project, nested on the Health Demographic and Surveillance System in Sleman, involving 549 elderly participants. The independence of these elderly people was measured using an Activities of Daily Living Scale questionnaire. Factors measured were cognitive (using the Mini-Mental State Examination questionnaire), psychological (using the Geriatric Depression Scale or Cornell Scale for Depression in Dementia questionnaires), economic (using the Financial Management Behavior Scale questionnaire), and nutritional status (using the Mini Nutritional Assessment questionnaire). The data were analyzed using the chi-square test, Fisher test, and Poisson test for bivariate analysis, while multivariate analysis using a logistic regression test. Results: The prevalence of elderly dependence was 14.03%. Elderly dependence was significantly related to age, job, residence, financial management, dementia, depression, malnutrition, and stroke disease in the bivariate analysis. However, after multivariate analysis, only age (>86 years) (PR = 4.31; 95% CI = 1.91–9.72), malnutrition (PR = 6.62; 95% CI = 3.79–11.57), and stroke (PR = 3.06; 95% CI = 2.03–4.61) were still shown to be related to elderly dependence. Conclusion: Increasing age, malnutrition, and stroke in elderly people lead to higher dependency in their ADLs.